(3GdMeGjI GdLRGFjI ddeSJgdc (B:s "(3OQGSI ebGQfI(B" /s - (3eQJLj, QGej RcQjG QeRjs ((3GdLjRI, LeghQjI eUQ GdYQHjI (B:s (3eQcR GdOQGSGJ GdYQHjI ddfTQ hGdJhRjY,s, 2019)
(3jJfGhd cJGH (B((3GdMeGjI GdLRGFjI ddeSJgdc(B) (3GdPj bGe HJCdjag (B((3QGej RcQjG QeRj eQJLj(B) (3aj MhGdj (B(229) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3MeGjI GdeSJgdc(B) (3eJVefG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd (B: (3eGgjI MeGjI GdeSJgdc aj GdTQjYI GdESdGejI hGdbGfhf, GdeHMK GdChd (B: (3eaghe hWHjYI MeGjI GdeSJgdc, GdeHMK GdKGfj (B: (3Mbhb GdeSJgdc hGdYdI ef GdMeGjI GdLRGFjI dg, GdaUd GdKGfj (B: (3GdLQGFe GdhGbYI Ydi Mbhb GdeSJgdc hLRGAGJgG aj GdTQjYI hGdbGfhf, GdeHMK GdChd (B: (3GdLQGFe GdeGSI HGdeSJgdc aj GdJTQjY GdadSWjfj, GdeHMK GdKGfj (B: (3GdLRGAGJ GdebQQI Ydi GdLQGFe GdhGbYI Ydi GdeSJgdc(B.s
(3HHdjhLQGajI (B: (3UaMI (B211-226.s
Keywords: (3MeGjI GdeSJgdcs -- (3bhGfjf hJTQjYGJs -- (3adSWjfs; (3GdZT hGdJOdjSs -- (3bhGfjf hJTQjYGJs -- (3adSWjfs; (3GdHjYs -- (3bhGfjf hJTQjYGJs -- (3adSWjfs; (3YbhO GdHjYs -- (3bhGfjf hJTQjYGJs -- (3adSWjfs; (3GdYdGeGJ GdJLGQjIs -- (3bhGfjf hJTQjYGJs -- (3adSWjfs; (3GdYbhO GdEdcJQhfjIs -- (3bhGfjf hJTQjYGJs -- (3adSWjfs; (3GdYbhHGJ GdHOjdIs -- (3adSWjfs; (3LQGFe GdZT s; (3LQGFe GdNOGYs; (3LQjeI GdEYdGf GdeVdds; (3GdGMJcGQ s; (3GdYbhHGJ GdSGdHI ddMQjIs